An Ag-loaded photoactive nano-metal organic framework as a promising biofilm treatment. (1st October 2019) - Arenas-Vivo, Ana; Amariei, Georgiana; Aguado, Sonia; Rosal, Roberto; Horcajada, Patricia
Graphical abstract: Abstract: Surface biofilm inhibition is still currently a considerable challenge. Among other organisms, Staphylococcus aureus is notable for its ability to form a strong biofilm with proved resistance to chemotherapy. Contamination of high-touch surfaces with S. aureus biofilm not only promotes disease spread but also generates tremendous health-associated costs. Therefore, development of new bactericidal and antiadhesive surface coatings is a priority. Considering that metal-organic frameworks (MOFs) have recently emerged as promising antibacterial agents, we originally report here the synthesis of a multi-active silver-containing nanoscaled MOF composite as a potential surface coating against S. aureus biofilm owing to a triple effect: intrinsic bactericide activity of the MOF, biocidal character of silver nanoparticles (AgNPs), and photoactivity after UVA irradiation. AgNPs were successfully entrapped within the benchmarked nanoscaled porous photoactive titanium(IV) aminoterephthalate MIL-125(Ti)NH2 using a simple and efficient impregnation-reduction method. After complete characterization of the composite thin film, its antibacterial and anti-adherent properties were fully evaluated. After UVA irradiation, the composite coating exhibited relevant bacterial inhibition and detachment, improved ligand-to-cluster charge transfer, and steady controlled delivery of Ag + . These promising results establish the potential of this composite as an active coating for biofilm treatment on high-touch surfaces (e.g., surgical devices, door knobs, and rail bars). Statement of Significance: Surface contamination due to bacterial biofilm formation is still a demanding issue, as it causes severe disease spread. One possible solution is the development of antifouling and antibacterial surface coatings. In this work, we originally propose the use of photoactive metal-organic frameworks (MOFs) for biofilm treatment. The novelty of this work relies on the following: i) the treatment of strongly contaminated surfaces, as previous studies with MOFs have exclusively addressed biofilm prevention; ii) this pioneering work reports both antiadherent effect, which removes the biofilm, and bacterial inhibition; iii) our original successful strategy has never been proposed thus far, involving the multi-active combination of 1) intrinsic antibacterial effect of a photoactive titanium-based nanoMOF, 2) immobilization of biocide silver nanoparticles, and 3) improved anti-bioadherent effect upon irradiation of the composite coating.